Development of E-Modules Based on Blended Learning in Class II English Subjects at Student One Islamic School - Arianto, Anugerahaning Meidy; Ibrahim, Nurdin; Hartono, Rudi (JENTIK : Jurnal Pendidikan Teknologi Informasi dan Komunikasi, 2024)
This research aims to: (1) developing digital teaching materials in the form of class II English e-modules, (2) analyze product feasibility and (3) determine the effectiveness of product development. This research uses the Bord and Gall development model which is integrated with Rowntree. In feasibility testing, assessments were carried out by 3 experts, namely learning design experts, media experts and material experts. The test results for instructional design experts were 86.15%, media experts 90.67% and material experts 84.67%, all in the very appropriate category. The research results show that the quality of the developed E-module is good in one-to-one trials (83.33%), good for small groups (87.14%), and very good for large groups (90.43%). The results of the effectiveness test were carried out by comparing the results of the pretest and posttest scores to obtain t test results with df = 22 and a significance level of 5% or 0.05 is obtained ttable = 2.074. It is known that tcount > ttable is 3.8758 > 2.0738. It was concluded that there was a significant difference in the results of the pretest and posttest and the application of the E module based on Blended Learning for Class II English Subjects at Student One Islamic School was declared effective.